2016
DOI: 10.1007/s00595-016-1446-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of ursodeoxycholic acid in the prevention of gallstone formation after laparoscopic sleeve gastrectomy

Abstract: The use of UCDA effectively reduced the incidence of CL after LSG in patients with morbid obesity. Dyslipidemia and rapid EWL in the first 3 months after LSG significantly predisposed patients to postoperative CL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 28 publications
1
12
0
7
Order By: Relevance
“…In our current study, UDCA was significantly decreased in both cholecystolithiasis and non-neoplastic polyps, suggesting that it may have a protective effect on the gallbladder. These results are consistent with previous reports showing that UDCA can prevent gallstones [ 18 , 19 ]. Notably, UDCA is positively correlated with age, but negatively correlated with white blood cell count and Neutrophil percentage.…”
Section: Discussionsupporting
confidence: 94%
“…In our current study, UDCA was significantly decreased in both cholecystolithiasis and non-neoplastic polyps, suggesting that it may have a protective effect on the gallbladder. These results are consistent with previous reports showing that UDCA can prevent gallstones [ 18 , 19 ]. Notably, UDCA is positively correlated with age, but negatively correlated with white blood cell count and Neutrophil percentage.…”
Section: Discussionsupporting
confidence: 94%
“…Diante do exposto, são propostas medidas de rastreamento e prevenção para formação de cálculos biliares e suas complicações. Quanto ao rastreamento, recomenda-se um exame de ultrassom nas primeiras seis semanas como exame de rotina após cirurgia bariátrica para detecção de cálculos biliares (ABDALLAH E, et al, 2017). Tem ganhado destaque como fator protetor para formação de cálculos biliares o uso do ácido ursodeoxicólico ou UDCA, reduzindo assim o risco de se desenvolver complicações de origem biliar (MACHADO FHF, et al, 2019).…”
Section: Revisão Bibliográficaunclassified
“…One of the most studied medications to prevent cholelithiasis formation is UDCA, a secondary bile acid that increases cholesterol solubility in hepatic bile [29]. Several randomized trials have shown that UDCA decreases bile lithogenicity, concluding that UCDA can effectively prevent cholelithiasis and the risk of cholecystectomy after bariatric procedures [30][31][32][33].…”
Section: Routine Postoperative Administration Of Ursodeoxycholic Acidmentioning
confidence: 99%